YOUTUBE AS A DA'WAH MEDIUM FOR THE ZOOMER GENERATION: By Habib Ja'far & Dr. Fahruddin Faiz "The Key To A Happy Life Is Self-Awareness And Knowing One's Limits." - Moch Farid Nuruz Zaman; Farhan Farhan (Jurnal Ilmiah Syi'ar, 2025)
This article examines the YouTube path as a means of da'wah for the younger generation, discussing the role of social media as a means of da'wah in the digital era, especially in spreading Islamic teachings for viewers born between 1997 and 2015 through platforms such as YouTube, Instagram, and Facebook. Along with the development of technology, social media has become a basic need that not only influences social interaction but also has an impact on the way da'wah is delivered. Habib Ja'far al-Hadar and Fahruddin Faiz are examples of figures who use digital media to convey religious messages to the younger generation. Habib Ja'far, through his relaxed and humorous style on the YouTube platform, has succeeded in attracting the attention of young people with inclusive and moderate da'wah content. Meanwhile, Fahruddin Faiz, with his gentle language style and philosophical perspective, provides a new understanding of important concepts in religion and life. This study uses a literature analysis method to explore the da'wah approach of the two figures, as well as explore the concept of youth as agents of social change. This article also highlights the important role of social media in reaching a wide audience and how this platform can effectively overcome the barriers of space and time in spreading da'wah.Habib Ja'far and Dr. Fachruddin Faiz chat about how the younger generation often gets caught up in the speed of life that makes them lose their meaning and purpose. They highlight that although technology and material luxuries can provide comfort, they do not guarantee happiness or satisfaction in life. The key to living a meaningful life is to have high self-awareness, know your limits, and set clear goals.